THE ROLE OF FRAMEWORK IN ENGLISH LANGUAGE TEACHING (ELT) IN ASEAN: VOICES FROM REGIONAL ENGLISH EDUCATORS - Tias, Silfia Asning; Tongjean, Waraporn (JP3 (Jurnal Pendidikan dan Profesi Pendidik), 2025)
This study examines the role of a framework in English Language Teaching (ELT) in ASEAN countries through the lens and experiences of regional English educators. Utilising a qualitative research design to examine three central questions: the frameworks used, the challenges of implementation and integration of the framework in classroom practice. The data collection was conducted through interviews with approximately 18 English educators from multiple regions in ASEAN countries. Findings bring attention to the frameworks which are commonly referenced, such as Communicative Language Teaching (CLT) and the Common European Framework of Reference (CEFR). The implementation is often shaped by contextual constraints, including facilities and infrastructure, educators’ competencies, learners’ proficiency and institutional or national policy. Additionally, the discussion reveals a diverse range of approaches influenced by local, national, and international ELT models. Teachers reported both benefits, such as improved clarity and coherence in lesson planning, as well as challenges, including mismatches between framework assumptions and classroom realities. The study highlights the importance of critical reflection in adapting the frameworks, emphasising the need for localised pedagogical strategies that empower educators to make context-sensitive decisions. These insights contribute to ongoing discussion on responsive ELT practices in linguistically and culturally diverse settings.